UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL (IPS) MENGGUNAKAN MODEL COOPERATIVE LEARNING PADA SISWA KELAS V SDN NO.06 TANJUNG SOKAN - Anuar, Anuar; Usman, Andi; Wibowo, Deki (JURNAL PENDIDIKAN DASAR, 2014)
The purpose of this research is to improve the student performance result on the subject Social Science through cooperative learning model, where the research its self was taken in grade V Public Elementary School 06, Tanjung Sokan. The method used in the research was the qualitative approach, with the result found that the number of student performance in learning process increase for about 65% (18 students) in the first cycle, and 75.50% (22 students) in the second cycle. In addition, the teacher performances also increased from score 41 or about 75% in the first cycle to score 45.5 or about 81.25% in the second cycle. It is found also that the student performance in first cycle increased for about 6.25%, with the number of student passed the subject was 16 students or 57.15% from 28 students. The second cycle shown that the numbers of student passed the subject was 23 students or 21.43%.Keywords: Cooperative Learning, Student Learning Result.